2008
DOI: 10.1111/j.1440-1819.2007.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

Nightmare disorder, dream anxiety, and subjective sleep quality in patients with borderline personality disorder

Abstract: Aims:  The aims of the present study were to examine the rate of nightmare disorder (ND) and to determine the levels of dream anxiety and subjective sleep quality in patients with borderline personality disorder (BPD). Another aim was to determine whether dream anxiety was associated with childhood trauma, dissociative experiences, and subjective sleep disturbance in BPD patients. Finally, the hypothesis as to whether BPD patients with ND exhibited a more severe clinical profile than those without ND, was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 28 publications
8
102
0
4
Order By: Relevance
“…Again, associations appear independent of comorbid depression. Complex associations between trauma, nightmares, and BPD are indicated (Claridge et al, 1998;Lereya et al, 2016;Semiz, Basoglu, Ebrinc, & Cetin, 2008). Recent prospective evidence suggests that nightmares could exacerbate reactions to early trauma increasing risk of subsequent BPD .…”
Section: Do Individuals With Bpd Significantly Differ From Controls Omentioning
confidence: 99%
See 1 more Smart Citation
“…Again, associations appear independent of comorbid depression. Complex associations between trauma, nightmares, and BPD are indicated (Claridge et al, 1998;Lereya et al, 2016;Semiz, Basoglu, Ebrinc, & Cetin, 2008). Recent prospective evidence suggests that nightmares could exacerbate reactions to early trauma increasing risk of subsequent BPD .…”
Section: Do Individuals With Bpd Significantly Differ From Controls Omentioning
confidence: 99%
“…Sleep problems may not only worsen symptom course in BPD but also heighten risk of suicide (Balestrieri et al, 2006;Winsper & Tang, 2014) and self-harm (Semiz et al, 2008) in this vulnerable population. Hence, mental health professionals should routinely assess the degree to which patients with BPD are experiencing sleep difficulties.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Semiz and colleagues [33] were the first to examine BPD and sleep without PSG recordings in their study of nightmare disorder, dream content, and sleep quality in a large clinical sample of BPD patients. They reported that 96 % of their group of 88 (48 female, 40 male) nondepressed BPD patients self-identified as poor sleepers, as compared to 12 % of controls.…”
Section: Self-report Studiesmentioning
confidence: 99%
“…The prevalence of BPD is approximately 1-2 % in the general population; BPD is more often diagnosed in women than in men and often co-occurs with Axis I disorders such as depression (96 %), anxiety disorders (64 %), posttraumatic stress disorder (65 %), substance abuse or substance dependency (64 %), ADHD (39 %), and eating disorders (53 %) (Bohus 2009). Interestingly, patients with BPD often report subjective sleep problems, especially insomnia, nightmares and dream anxiety (Bastien et al 2008;Semiz et al 2008). Furthermore, it has been suggested that the disturbed sleeping behaviour may alter the regulation of emotion in these patients (Harty et al 2010), thus shaping the phenotype of the disorder.…”
Section: Introductionmentioning
confidence: 99%